Efektivitas Antiseptik Ekstrak Jeruk Nipis dan Lidah Buaya Terhadap Jamur Candida Albicans - Lukky Jayadi; Sandry Kesuma (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
The use of hand antiseptics in the form of preparations among the community has become a lifestyle. Several hand antiseptic preparations can be found in the market. How to use it is to be dropped on the palm of the hand, then flattened on the surface of the hand. Alcohol is widely used as an antiseptic to disinfect surfaces and clean skin, but not for wounds. Alcohol as an antiseptic has bactericidal activity, works against various types of bacteria, viruses and fungi. This study aims to make an antiseptic with lime and aloe vera extracts that can kill the fungus candida albicans. In this study, the pH of the preparation was measured, the pH was 5 and for determining the specific gravity, the specific gravity was 0.9736 g/ml. The test is carried out using the percentage kill method at two contact times, namely 30 and 60 seconds. The percentage kill results for antiseptic preparations with lime and aloe vera extracts at the two contact times were 99.9% percentage kill. There is an impact of using an antiseptic with an active ingredient of alcohol with the addition of lime and aloe vera extracts on pH, specific gravity and fungal killing power. Keywords: Antiseptic, Lime, Aloe Vera, Candida Albicans